Implementation of Learning Supervision in Improving Teacher Performance in Schools - Ade Sentia Arsy Sabila; Ahmad Zainuri (Examinations: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Learning supervision is an important strategy for improving teacher performance and the quality of learning in schools. Teachers, as the main actors in the learning process, require continuous professional guidance to enhance their ability to plan, implement, and evaluate learning effectively. This study aims to describe the implementation of learning supervision in improving teacher performance in schools. The research employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The results indicate that learning supervision is implemented through interconnected stages, including planning, implementation, and follow-up. Learning supervision conducted through a collaborative and developmental approach contributes to improvements in teacher performance, particularly in lesson planning, the use of varied teaching methods, and systematic learning evaluation. Furthermore, learning supervision encourages teacher professionalism and awareness of continuous improvement in instructional practices. Therefore, well-planned and sustainable learning supervision plays a significant role in enhancing teacher performance and overall educational quality in schools.